(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: There is a wide consensus that the COVID-19 pandemic not only affects physical health, but also mental health and well-being. It can lead to heightened levels of distress and cause anxiety, fear, denial or depressive symptoms among the military personnel. Objective: To assess the impact of COVID-19 on mental health among the confirmed cases of Armed Forces Personnel of Sylhet and Jalalabad Cantonment. Methods: A total of 180 participants were selected using convenience sampling. The mental health was assessed by a 22 items Impact of Event Scale-Revised (IES-R) adopted from Horowitz 1979. The scale comprised of 3 subscales of intrusion, avoidance and hyper-arousal which represents major symptoms of post-traumatic stress. Stress for job, financial issue, home and feeling horrified or helpless due to the COVID-19 were also assessed. Results: This study revealed that 47.7% were experiencing moderate distress whereas 30.1% were experiencing high to severe post-COVID stress. Mean stress was observed as 41.5 ± 19.0. Mean Intrusion (34.9 ± 22.9) and Hyper-arousal (27.8 ± 23.5) depicted mild to moderate but Avoidance (58.5 ± 20.9) revealed a higher level of stress. A majority were not at all stressed for their job (56.7%) or financial issue (49.4%). But stress for family (28.4%), feeling horrified (35.6%) and helpless (36.6%) were quite high. Conclusion: The study observed a moderate to high prevalence of mental health symptoms among the COVID affected personnel which was considered to be significant and demands appropriate intervention. JAFMC Bangladesh. Vol 17, No 2 (December) 2021: 7-11